Uma arqueologia do imaginário do corpo na Revista Junior - Lopes, Paulo Aldemir Delfino (2014)
This dissertation, based on theoretical assumptions of Discourse Analysis of French line, especially in studies undertaken by Michel Pêcheux, Michel Foucault and Jean-Jacques Courtine, attempts to identify the imaginary body presented in textual and pictorial statements materialized in JUNIOR magazine, monthly publication by MixBrasil publisher, which focuses on the Brazilian gay public. The magazine, understood as a disciplinary device outlet, influences its readers by presenting a pedagogy based on a truth desire of being gay that pursues, above all, a frame of the subject in a body that has the muscly standard as a sign of virility and beauty. The body culture is presented as a mean for access to forms of subjectivities that would ensure visibility to gay men. The process of subjectivation is thought, therefore, from the body transformation techniques, which, based on the discourse from various discursive formations, update the principle of "care of the self" and incite the subject-readers to the consumption of products to beautify their body, diets and workout exercises to optimize the muscle gain, and also to submit themselves to invasive aesthetic treatments, like plastic surgery. Through the notion of discourse memory, we realized the appearance of the body in the media as a new event that restores discursive and non-discursive practices linked to hedonism and narcissism individualist culture in which subjects, under the auspices of individual freedoms, become, in fact, subjected to the prevailing aesthetic standards.